Pengaruh Financial Distress, Profitabilitas, Audit Tenure, Dan Audit Complexity Terhadap Audit Report Lag (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang terdaftar di Bursa Efek Indonesia pada Tahun 2020-2024) - Atika Putri Setiawan; Asih Handayani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze and examine the effect of financial distress, profitability, audit tenure, and audit complexity on audit report lag. The research employs a quantitative approach. The population consists of 162 companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used is purposive sampling, resulting in 95 companies that meet the criteria and serve as the research sample. The analysis method applied is multiple linear regression, processed using Eviews 13. The findings indicate that financial distress, profitability, audit tenure, and audit complexity simultaneously influence audit report lag. However, partially, financial distress and audit complexity have no significant effect on audit report lag, while profitability and audit tenure significantly affect audit report lag.